ADIRAMA: PRODUCTION AND USE OF THE SALT ADDITIVE OF MADURA - Rahmad Fajar Sidik; Makhfud Efendy (JURNAL PENA SAINS, 2019)
Salt of Madura is a unique product and dominates in the local and regional markets. It is the result of sweat and sweat from local youth in seeking and living life. The process of using salt additives is an idea that arises because naturally the people of Madura have used it, which is adding trusion in terms of facing the water process that it has. The sea water that experiences the process of adding additives has the highest NaCl, ceramics land 96.02%, LDPE land 95.72% and soil area 93.81%. Whereas those who were not treated had lower NaCl, 93.94% ceramics, LDPE 92.65% and soil 87.78%. And for some treatments for some treatments heavier than others, namely ceramic additives 47.65 Kg, additive LDPE 49.15 Kg, and additive soil 32.50 Kg. While the soil that is not treated is mostly lower in salt, non-additive ceramics 46.75Kg, non-additive LDPE 50.75 Kg and non-additive soil 26.95 Kg.